Answer:
q = -8, q = 6
Step-by-step explanation:
[tex]6 {q}^{2} - 4q = 5 {q}^{2} - 6q + 48[/tex]
Move everything to the left of the =:
[tex]6 {q}^{2} - 4q - 5 {q}^{2} + 6q - 48 = 0[/tex]
Combine terms with the same power of q:
[tex] {q}^{2} + 2q - 48 = 0[/tex]
Now you need to find two numbers that multiply to make -48 and add to make 2.
The numbers I found are 8 and -6.
Then write two parentheses like this:
[tex](q + 8)(q - 6) = 0[/tex]
Then you need to look at each parenthesis individually. See what q would have to be for the parenthesis to equal 0.
For the the first one, q would have to be -8
For the second one, q would have to be 6
These are the solutions for q.